Home Based Telemedicine System For Respiratory Disorder Patients - NANDHINI P; HARI KRISHNAN G; UMASHANKAR G (International Journal of Pharma and Bio Sciences, 2015)
In this paper we have focused on home monitoring system for patients with respiratory illness. It involves the measurement of the heart rate, temperature and the respiration rate of the patient. We use a zigbee based wireless link to the doctor’s PC for long-term data acquisition. This project also includes an automatic syringe infusion pump used to deliver medicine to the patient. The range of the parameters is initially set by the doctor’s, in case of any deviation from the set values, an alarm is indicated on the doctor’s side and simultaneous delivery of medication to the patient is carried out by the syringe pump. This system is highly used in conditions where there is no constant need for a medical staff to attend the patient.